KINERJA TIM KENDALI MUTU KENDALI BIAYA CABANG SURAKARTA DALAM PENGENDALIAN MUTU DAN BIAYA PADA PROGRAM JAMINAN KESEHATAN NASIONAL - Sholahuddin Sanjaya; Dwi Handono Sulistyo; Julita Hendrartini (Departemen Kebijakan dan Manajemen Kesehatan, Fakultas Kedokteran, Kesehatan Masyarakat, dan Keperawatan, Universitas Gadjah Mada, Yogyakarta Jl. Farmako Sekip Utara Yogyakarta 55281 Telp 0274-547490, 2019)
Background: Indonesia in 2014 implemented the National Health Insurance (JKN) program. The implementation of the comparison between contribution and health insurance expenditure in the Surakarta Branch Office is not optimal. The Coordinating Team in TKMKB plays an important role in JKN quality and cost control. Hence, we need to evaluate the performance with the TKMKB Surakarta Branch coordination team. Objective: To evaluate the performance of TKMKB Surakarta Branch Coordination Team in quality and cost control of JKN program and to identify performance inhibiting factors. Methods: The research was descriptive with case study design using qualitative approach focusing on developing the description and depth analysis about Coordination Team performance on national health insurance program at Surakarta Branch Office. Performance was assessed based on the implementation of the job description. Data were collected using interviews and document review. Results: The utilisation review task was not standardised yet because it was only implemented once and there was no monitoring and follow-up of utilisation review indicators, the discussion of the problem and the evaluation of the policy has not been in accordance with the standards because the recommendation issues have not been in accordance with the issues raised. The socialisation of authority, ethical guidance and professional discipline of health personnel have not been up to standard because they are not conveyed to all members of professional organisations. Factors that hamper performance were limited time, lack of data access, and facilitation. Conclusion: The performance of the Coordination Team on the task of utilisation review has not been optimal yet, the task of discussing the problem and the evaluation of the policy has not been optimal, and in the task of authority socialisation, ethics coaching and health professional discipline has not been optimal. Factors that hinder performance were limited time, lack of data access, and facilitation of TKMKB.